BoneMicro-CT Assessments in an Orchidectomised RatModel Supplemented with Eurycoma longifolia - Ramli, Rosmaliza; Khamis, Mohd Fadhli; Shuid, Ahmad Nazrun (Hindawi Publishing Corporation, 2012)
Recent studies suggested that Eurycoma longifolia, a herbal plant, may have the potential to treat osteoporosis in elderly male. This study aimed to determine the effects of Eurycoma longifolia supplementation on the trabecular bone microarchitecture of orchidectomised rats (androgen-deficient osteoporosis model). Forty-eight-aged (10–12 months old) Sprague Dawley rats were divided into six groups of sham-operated (SHAM), orchidectomised control (ORX), orchidectomised + 7mg/rat testosterone enanthate (TEN) and orchidectomised + Eurycoma longifolia 30 mg/kg (EL30), orchidectomised + Eurycoma longifolia 60 mg/kg (EL60), orchidectomised + Eurycoma longifolia 90 mg/kg (EL90). Rats were euthanized following six weeks of treatment. The left femora were used to measure the trabecular bone microarchitecture using micro-CT. Orchidectomy significantly decreased connectivity density, trabecular bone volume, and trabecular number compared to the SHAM group. Testosterone replacement reversed all the orchidectomy-induced changes in the micro-CT parameters. EL at 30 and 60 mg/kg rat worsened the trabecular bone connectivity density and trabecular separation parameters of orchidectomised rats. EL at 90 mg/kg rat preserved the bone volume. High dose of EL (90 mg/kg) may have potential in preserving the bone microarchitecture of orchidectomised rats, but lower doses may further worsen the osteoporotic changes.